Differences in Children’s Social Development: How Migration Background Impacts the Effect of Early Institutional Childcare Upon Children’s Prosocial Behavior and Peer Problems - Konrad-Ristau, Kira; Burghardt, Lars (Frontiers in Psychology, 2021)
This article focuses on the early years of children from immigrant families in Germany. Research has documented disparities in young children’s development correlating with their family background (e.g. immigrant or ethnic minority status), making clear the importance of early intervention. Institutional childcare – as an early, potentially compensatory, intervention for children at risk – plays an important role in Germany, as 34.3 % of children below the age of three and 93 % of children above that age are in external childcare. This paper focuses on the extent to which children from families with a background of migration differ in their social development when considering their age of entry into early external childcare (and thus its duration). Data from the infant cohort study of the German National Educational Panel Study (NEPS, N = 1 846) is used to analyze the impact of early institutional childcare before the age of three years on children’s social competence at the age of five years, controlling for gender, siblings, temperament, home learning activities, and socioeconomic status. Results show the effects of duration of early external childcare on peer problems for children from families with a background of migration, in such a way that children who attend early external childcare for more than one year before the age of three show less problem behavior with peers than those who attend for less than a year. Our results imply the presence of the so-called compensatory hypothesis, as we find (positive) effects for children with a migration background. These findings have equity implications for children with a migration background living in Germany, especially as the proportion of these children is trending upwards.